2009
DOI: 10.1055/s-0029-1210497
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gonads of Male and Female Offspring of Mice Receiving a Continuous Intravenous Infusion of Human Chorionic Gonadotropin during Gestation

Abstract: In male offspring of mice given a continuous intravenous infusion of 24 IU/day hCG from days 15 to 19 of gestation (hCG-primed mice), the number of Leydig cells/testis at 15 days of age was similar to the value at 10 days, whereas the cells were decreased in number in the controls at 15 days. Mitotic rate of the interstitial tissue in 30-day-old, hCG-primed mice was lower than in the controls. In seminiferous tubules of hCG-primed mice, intratubular spaces were formed at 15 days, while the spaces in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…hCG acts as an LH surrogate and stimulates replication of testicular Leydig cells and testosterone synthesis to promote male sexual differentiation at a critical time in sexual differentiation of the male fetus [Huhtaniemi et al, 1977;Cunningham et al, 2005]. High-dose hCG exposure to mice offspring induce abnormal male and female gonadal development [Takasugi et al, 1985;Matzuk et al, 2003]; therefore, exposure to excess hCG has the possibility to cause ambiguous genital differentiations of human fetuses. In addition, the cytoplasm of Hofbauer cells is coarsely vacuolated during early pregnancy; however, as gestation progresses, the vacuoles decrease in number and size [Castellucci and Kaufmann, 2006].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hCG acts as an LH surrogate and stimulates replication of testicular Leydig cells and testosterone synthesis to promote male sexual differentiation at a critical time in sexual differentiation of the male fetus [Huhtaniemi et al, 1977;Cunningham et al, 2005]. High-dose hCG exposure to mice offspring induce abnormal male and female gonadal development [Takasugi et al, 1985;Matzuk et al, 2003]; therefore, exposure to excess hCG has the possibility to cause ambiguous genital differentiations of human fetuses. In addition, the cytoplasm of Hofbauer cells is coarsely vacuolated during early pregnancy; however, as gestation progresses, the vacuoles decrease in number and size [Castellucci and Kaufmann, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal plasma concentrations of total hCG are only 3% of the maternal plasma levels, ranging from 30 to 2,800 mIU/ml between 8 and 20 weeks of gestation [Clements et al, 1976]. Circulating hCG in fetal blood is necessary for the differentiation of the fetal genitalia; therefore, excess hCG may induce aberrant genital differentiation of the fetus [Huhtaniemi et al, 1977;Takasugi et al, 1985;Matzuk et al, 2003]. We thus hypothesized that macrophages in placental villi regulate hCG to prevent the fetus from excess maternal hCG and the peculiar cytoplasmic vacuoles are related to the cell-specific function of Hofbauer cells.…”
mentioning
confidence: 99%
“…It has been reported that the pro-inflammatory cytokines in plasma and ascitic fluid can lead to reproductive failure and other adverse pathologies in the patients with OHSS [249]. In addition, excessive hCG stimulation can cause multiple defects in the differentiation of the fetal gonad [250,251]. HMGB1 has dual roles in sterile inflammation.…”
Section: Reception and Rejection Roles Of Sterile Inflammationmentioning
confidence: 99%
“…hCG promotes male sexual differentiation in the first trimester, and excess hCG is teratogenic to fetal gonadal tissues. Continuous intravenous infusion of high‐dose hCG into pregnant mice results in seminiferous tubules with a disorganized germinal epithelium and impaired spermatogenesis in male offspring (Takasugi et al . 1985).…”
Section: Introductionmentioning
confidence: 99%